Metal with surface treated by silane coupling agent, treatment method and high-frequency high-speed signal transmission base material
By using non-hydrolyzed silane coupling agent and anhydrous organic solvent on the metal surface to form a nano-scale coupling agent layer and perform heat cross-linking treatment, the problem of water release of the coupling agent layer on the metal surface is solved, and the metal and resin are significantly improved The interface bonding strength and dielectric properties meet the needs of high-frequency and high-speed signal transmission.
Patent Information
- Application Number
- CN202411527564.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-11
AI Technical Summary
Prior Art When applying silane coupling agent on metal surfaces, it is impossible to avoid the continuous release of water from the coupling agent layer during the preparation and use of metal resin composite materials, resulting in a decrease in interface bonding strength and unstable dielectric properties, especially at high levels. There are major hidden dangers in frequency high-speed signal transmission.
By combining the hydroxyl group or oxide on the metal surface in anhydrous organic solvent, a nano-thick coupling agent layer is formed, and the coupling agent layer is cross-linked by heat treatment, thereby reducing the hydroxyl content of silicon and improving the hydroxyl group. Coupling agent molecules are involved in building the ratio of "molecular bridge" between metal and resin.
It realizes the control of the thickness of the metal surface coupling agent layer on the nanometer order, reduces the silicon hydroxyl content in the coupling agent layer, significantly improves the interfacial bonding strength and dielectric performance stability of metal and resin, and meets high-frequency and high-speed signals. Transmission requirements.
Smart Images

Figure CN119421342A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for treating a metal surface with a silane coupling agent, and also relates to a metal material after the surface treatment; and also relates to the application of the material in a high-frequency and high-speed signal transmission substrate. Background Art
[0002] In order to ensure the bonding strength and stability between metal and any substrate formed by organic materials, silane coupling agents are usually required. The general structural formula of silane coupling agent molecules is Y-R'-Si(OR) 3, where the OR silane alkoxy active group directly connected to -Si- acts as an inorganic end, chemically reacts with the hydroxyl group on the metal surface or the hydroxyl group on the oxide to form a Si-O covalent bond; the active group Y connected to the alkylene group acts as an organic end, chemically reacts with the organic resin, generates hydrogen bonds, or increases the interaction with the resin through physical entanglement. Therefore, the silane coupling agent can build a "molecular bridge" between metal and resin materials with very different properties, improve the interface structure between metal and resin materials, and enhance the interface bonding strength. From the perspective of the mechanism of building a "molecular bridge", only a few layers of silane coupling agent molecules closest to the metal surface can form covalent bonds with the metal surface, that is, the thickness of the coupling agent layer that actually plays a bonding role only needs to be a few nanometers. In the prior art, when using silane coupling agents, they are usually dissolved in ethanol / water for hydrolysis before being applied to the metal surface. However, when the silane coupling agent is dissolved in an alcohol-water solution, hydrolysis / alcoholization will inevitably occur. OR in its molecular structure is a hydrolyzable group, which will be hydrolyzed in alcohol / water to generate silanol, which will then interact with the metal surface to produce a bonding effect. Therefore, on the one hand, the silane coupling agent layer formed on the metal surface by the existing treatment methods such as coating, brushing, spraying, electroplating, and solution dipping is generally thick and unevenly distributed. For example, patent CN103717011A reports that the thickness of the silane coupling agent layer on the copper foil surface is 1 to 10 microns. On the other hand, since the metal interface that can participate in the reaction is limited, after the coupling agent solution is applied, most of the silane coupling agent molecules in the coupling agent layer are attached to the metal surface only by physical adsorption, and only a small part can achieve chemical bonding on the metal interface, which not only fails to build a "molecular bridge" between the metal and the resin, but a large number of silanols generated by hydrolysis in the above steps that do not participate in the interfacial chemical reaction are more likely to dehydrate and condense to form siloxanes, resulting in the condensation and dehydration reaction between silanol groups becoming a hidden water source in the metal and resin composite material. For example, in patent CN111465715A, a metal-resin joint body of a composite laminate and a method for manufacturing the same are proposed, which is combined by reacting the silanol groups generated by hydrolysis of the silane coupling agent or its oligomerized silanol groups with the hydroxyl groups on the surface-treated side of the metal substrate, so that the metal substrate can be combined with the resin coating layer through the structure of the silane coupling agent.
[0003] The excess and unevenly distributed physical adsorption coupling agent in the composite material is very detrimental to the interfacial bonding strength between the metal and resin materials and the dielectric stability of the composite material, which seriously affects the application of the composite material as a signal transmission substrate. With the growing demand for high frequency and high speed of communication signals, on the one hand, under the influence of the skin effect of high-frequency signals, in order to ensure the integrity of high-frequency signal transmission, it is necessary to use metals with ultra-low surface roughness, and ultra-low surface roughness will cause a significant decrease in the interaction area between the metal and resin interface, making the composite material interface bonding very difficult. The physically adsorbed silane coupling agent that does not participate in the construction of the "molecular bridge" between the metal and the resin at the interface is an important reason for the decline in interfacial bonding performance. On the other hand, since the signal transmission rate is inversely proportional to the square root of the dielectric constant of the substrate, high-speed and low-latency signals require the transmission substrate to have a very low dielectric constant. Physically adsorbed coupling agents will undoubtedly increase the dielectric constant of the substrate. More importantly, during the service of the device, the water released due to the condensation between the silanol groups of the silane coupling agent will inevitably cause the interfacial dielectric constant to increase and reduce the reliability of the metal-resin composite substrate. Especially when the signal frequency enters the 6G terahertz field, since the vibration frequency of water molecules is equivalent to the signal transmission frequency, the local water enrichment at the metal-resin interface caused by the hidden water source in the silane coupling agent and the resulting anodized filaments will cause great damage to the stability and safety of the preparation and operation of the 6G device.
[0004] Strictly controlling the silanol content in the silane coupling agent and ensuring that the coupling agent at the metal-resin interface participates in the construction of a "molecular bridge" is the key to solving the high-strength bonding between ultra-smooth metal and resin, and making the composite material meet the requirements of high-frequency and high-speed signal transmission substrates represented by 6G. However, there is currently no public report on controlling the silanol content in the silane coupling agent layer on the metal surface. Therefore, developing new metal surface treatment processes and how to eliminate the hidden dangers of water sources in the coupling agent are urgent issues that need to be solved for metal-resin composite materials to meet the needs of high-frequency and high-speed signal transmission in the field of electronic communications. Summary of the invention
[0005] The present invention aims at the defect that the existing treatment method of coating silane coupling agent on metal surface cannot avoid the continuous release of water from the coupling agent layer during the preparation and use of metal-resin composite materials, and provides a treatment method for controlling the thickness of the coupling agent layer on the metal surface at the nanometer level, reducing the content of silanol in the coupling agent layer, and increasing the proportion of coupling agent molecules in the layer participating in the construction of the "molecular bridge" between metal and resin. The method uses a non-hydrolyzable silane coupling agent to combine with the hydroxyl or oxide on the metal surface in an anhydrous organic solvent to form a coupling agent layer with a nanometer thickness, thereby avoiding a large amount of unreacted silanol in the coupling agent layer, and also uses a heat treatment method to crosslink the nano coupling agent molecules on the metal surface. The cross-linked coupling agent layer with a nanometer thickness can not only give the metal good oxidation resistance, but also improve the compatibility of the metal and the resin, thereby significantly improving the interfacial bonding strength between the metal and the resin. The metal surface coupling agent treatment method described in the present invention not only reduces the amount of coupling agent used, but more importantly solves the problem of water release from the metal surface due to the condensation of silanol in the coupling agent. The long-term stability of the mechanical and dielectric properties of the metal material prepared by the above-mentioned metal surface coupling agent layer treatment method and the resin after being compounded is improved, which can meet the requirements of high-frequency and high-speed signal transmission substrates represented by 6G.
[0006] A metal treated with a silane coupling agent on the surface, comprising a modified layer composed of a silane coupling agent on the surface, the thickness of the modified layer is in the range of 1-100 nm, and the -Si(OR) 3 The group was not hydrolyzed.
[0007] The proportion of the silane coupling agent that has not been hydrolyzed is at least 90%, preferably at least 95%, and more preferably at least 98%.
[0008] The thickness range is preferably 1-30 nm.
[0009] The metal is copper, magnesium, aluminum, titanium, iron, zinc or an alloy thereof; the alloy refers to an alloy in which the corresponding metal is the main component, accounting for more than 20wt%, more than 50wt%, and preferably more than 80wt%.
[0010] The metals also include metal or non-metal elements such as carbon, silicon, manganese, chromium, tungsten, molybdenum, phosphorus, titanium, vanadium, nickel, zirconium, and boron.
[0011] The general formula of the silane coupling agent is: Y-R'-Si(OR) 3 ;
[0012] Y is an organic group, which may be one of an amino group, a nitro group, a carboxyl group, an ester group, a hydroxyl group, an alkenyl group, an ether group, a sulfonic acid group, a mercapto group, an acryloxy group, a peroxyurea group, and a carbonyl alkoxy group;
[0013] R' can be H or a branched or unbranched alkyl group containing 1 to 20 carbon atoms;
[0014] R can be an alkoxy group, an aryloxy group, an acyl group, or a chloro group.
[0015] The silane coupling agent is one or more of vinyl coupling agent, hydroxyl coupling agent, amino coupling agent, sulfur-containing silane coupling agent, epoxy silane coupling agent and alkyl silane.
[0016] A metal-resin composite is a composite of a resin on the other side of the modified layer on the metal treated with the surface silane coupling agent.
[0017] The resin is a single type of resin or a resin composition; the resin includes a main resin and may or may not include a reinforcing material.
[0018] The resin is a thermoplastic or thermosetting resin.
[0019] The method for manufacturing the metal treated with the surface silane coupling agent comprises the following steps:
[0020] Step 1, polishing the metal surface;
[0021] Step 2, placing the obtained metal in an organic solvent containing a silane coupling agent for a temperature-raising reflux reaction; the water content in the organic solvent is less than 0.1%.
[0022] Step 3, the metal is heated after the reaction is completed.
[0023] The concentration range of the silane coupling agent in the anhydrous organic solvent is 0.001-1 wt %.
[0024] The temperature rising and reflux reaction time is 3-300 min, preferably 100-240 min.
[0025] Before the polishing treatment, the method further includes the step of pre-treating the metal, wherein the pre-treatment step includes one of dewaxing, degreasing, activating and cleaning; and after the polishing treatment, the metal can be placed in an organic solvent for reflux to remove residual water; and the method further includes the step of dewatering the organic solvent.
[0026] A method for processing a metal-resin composite comprises the following steps:
[0027] Place the surface treated metal in a mold, set the mold temperature to be above the glass transition temperature of the resin and below the melting temperature, then inject the resin into the mold to combine with the metal to form a metal-resin composite material, and hold the pressure for 5-20 seconds;
[0028] The metal-resin composite material is left in the mold, and the metal-resin composite material is demoulded after the temperature is lowered from the original temperature to 20° C. below the glass transition temperature of the resin material at a rate higher than 100° C. / s.
[0029] A printed circuit board substrate for high-frequency and high-speed signal transmission includes a metal-resin composite.
[0030] Beneficial Effects
[0031] The research of the present invention shows that the water contact angle of the coupling agent layer on the metal surface is closely related to the interfacial bonding strength of the metal-resin composite material. The principle is as follows: the closer the water contact angle of the coupling agent layer uniformly distributed on the metal surface is to the contact angle of the organic resin, the better the compatibility of the two. The good compatibility makes it easy for the organic resin to infiltrate the metal surface during processing, and achieve close contact with the coupling agent from the molecular level, providing space guarantee for further bonding reactions of the resin molecules and the coupling agent functional groups. The uniform distribution of the nanometer-thick coupling agent layer on the above-mentioned metal surface is achieved by reacting the non-hydrolyzable silane coupling agent with the metal surface hydroxyl or oxide. Since the silane coupling agent is not hydrolyzed before reacting with the metal surface, the number of unreacted silanol groups in the coupling agent layer is very small. In the subsequent preparation and application of the composite material, it can be avoided that a small amount of water molecules formed by the condensation of the coupling agent on the metal surface causes the interface dielectric constant to increase, thereby interfering with the high-speed transmission of high-frequency signals, and water molecules induce the production of anodized wires that cause circuit boards to fail and other hidden dangers. Compared with the metal treated with the conventional hydrolyzed silane coupling agent, the metal with the nanometer-thickness silane coupling agent layer on the surface has a greatly improved interfacial bonding strength with the organic resin. At the same time, the oxidation resistance of the nanometer-thickness silane coupling agent layer to the metal is also significantly enhanced than that of the conventional hydrolyzed silane coupling agent layer. These advantages make the method for constructing the metal surface nano-coupling agent layer provided by the present invention and the metal substrate prepared by this method particularly suitable for application in the field of high-frequency and high-speed signal transmission materials, achieving a good combination of metal and resin materials. Improve the reliability of the mechanical, electrical and dielectric properties of metal-resin composite materials to meet the requirements of high-frequency and high-speed signal transmission substrates represented by 6G. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a comparison chart of the metal-resin composite interface bonding strength between Example 1 of the present invention and Comparative Example 2.
[0033] Figure 2 This is a contact angle photograph of the metal surface treated in Example 1 of the present invention.
[0034] Figure 3 This is a contact angle photograph of the metal surface treated in Example 2 of the present invention.
[0035] Figure 4This is a contact angle photograph of the metal surface treated in Comparative Example 1.
[0036] Figure 5 This is a contact angle photograph of the metal surface treated in Comparative Example 2. DETAILED DESCRIPTION
[0037] The present invention discloses a method for constructing a metal surface nano-coupling agent layer and a metal material made by using the method. The metal surface coupling agent layer is formed by combining a non-hydrolyzable silane coupling agent with a metal surface hydroxyl or oxide in an anhydrous solution, and has the characteristics of uniform distribution of the coupling agent on the metal surface, a layer thickness of less than 100 nanometers, and extremely low content of silanol in the layer. Compared with the traditional method of forming a metal surface coupling agent layer by coating a hydrolyzed silane coupling agent, the present invention can significantly improve the bonding strength between metal and resin, and the anti-oxidation property of the coupling agent layer on the metal surface is also greatly improved, and the interfacial bonding strength between metal and organic substrate is significantly improved. Controlling the thickness of the metal surface silane coupling agent layer at the nanometer level not only reduces the amount of coupling agent used, but more importantly, solves the problem of water release from the metal surface due to condensation of silanol of the coupling agent. The treatment method of the metal surface nano-coupling agent layer is applied to the fields of electronic materials such as copper-clad laminates and chip packaging carriers, which can improve the long-term stability of the mechanical and dielectric properties of the material during service. The metal surface coupling agent layer construction method of the present invention is suitable for industrial production.
[0038] The treatment method is a treatment method for forming a nano-coupling agent layer on the surface of a metal substrate, comprising the following steps: (1) electrochemical polishing is used to perform sub-nanometer-level flattening treatment on the surface of the cleaned metal substrate, (2) the polished metal substrate is dried and then refluxed in an anhydrous organic solvent containing a non-hydrolyzable silane coupling agent to form a nano-thick coupling agent layer on the metal surface, and (3) heat treatment is used to cross-link the coupling agent layer on the metal surface. The thickness of the nano-coupling agent layer on the metal surface is quantitatively measured by an XPS depth analysis detection method.
[0039] The metal treated with a silane coupling agent in the present invention refers to a metal surface having a silane coupling agent layer, wherein -Si(OR) in the molecular structure 3 The group is not hydrolyzed, does not contain -Si-OH groups, and does not undergo dehydration condensation reaction with -OH groups on the metal surface.
[0040] The metal involved in the present invention can be copper, magnesium, aluminum, titanium, iron, zinc or alloys thereof. More specifically, the alloy here refers to a material with the corresponding metal as the main component (more than 20wt%, more than 50wt%, preferably more than 80% by mass); in addition, the metal material can also contain metal or non-metal elements such as carbon, silicon, manganese, chromium, tungsten, molybdenum, phosphorus, titanium, vanadium, nickel, zirconium, boron, etc.; the metal material can be in the form of block material, sheet, plate, foil, powder.
[0041] The silane coupling agent involved in the present invention can be one or more of a vinyl coupling agent, a hydroxyl coupling agent, an amino coupling agent, a sulfur-containing silane coupling agent, an epoxy silane coupling agent, and an alkyl silane.
[0042] It has the general formula: Y-R'-Si(OR) 3 .
[0043] Y is an organic group, which may be an amino group, a nitro group, a carboxyl group, an ester group, a hydroxyl group, an alkenyl group, an ether group, a sulfonic acid group, a mercapto group, an acryloxy group, a peroxyurea group, or a carbonyl alkoxy group.
[0044] R' may be H or a branched or unbranched alkyl group containing 1 to 20 carbon atoms.
[0045] R can be an alkoxy group, an aryloxy group, an acyl group, or a chloro group.
[0046] More specifically, without particular limitation, the silane coupling agent in the present invention may refer to: vinyl trimethoxysilane, vinyl triethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl methyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-glycidoxypropyl triethoxysilane, p-phenylenediyl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl Trimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminopropyltrimethoxysilane hydrochloride, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-isocyanatepropyltriethoxysilane, dithioltriazinepropyltriethoxysilane, etc.
[0047] The thickness of the silane coupling agent layer here is 1-100nm, and can also be any range formed between values such as 2nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, etc., preferably less than 30nm. Quantitative determination by XPS depth analysis detection method. The compatibility of the metal with a nano-thickness coupling agent layer on the surface and the composite resin is quantitatively characterized by a contact angle detection method. Taking the copper sheet treatment experiment as an example, the water contact angle of the metal surface before the coupling agent reflux treatment after polishing is 24-25°, and the water contact angle of the surface after the coupling agent treatment is 58-110°. The contact angle can be regulated by the compounding of different types of coupling agents as needed. The surface water contact angle is close to the water contact angle of the resin to be combined, for example, the contact angle difference is less than 40°, less than 30°, less than 20°, less than 10°, and less than 5°.
[0048] In the above-mentioned treatment method, the main step is to optionally pre-treat the metal surface, such as: one of dewaxing, degreasing, activation, and cleaning. For example, the metal can be degreased and deoiled, and the metal can be cleaned in an ultrasonic wave with various solvents commonly used by technicians in the field to remove the oil on the metal surface. Then the metal is placed in a solvent and the metal surface is washed under ultrasonic conditions. The solvent can be ethanol or acetone. After the pre-treatment, the metal surface can also be polished. In a typical embodiment, the metal is pre-treated on the surface and then placed in an electrolytic cell as an anode for polishing. The polishing liquid is a 55wt% phosphoric acid solution containing 0.1-1wt% ascorbic acid and 0.1-1wt% ethylene thiourea, which is preheated to 55°C, and then electrolyzed at a constant voltage of 10-100V for 1-120 minutes. After polishing, it is washed with water, blown dry with cold wind, and stored in an anhydrous organic solvent to prevent air oxidation of the metal surface.
[0049] The polished metal substrate is placed in an anhydrous organic solvent containing 0.001-1wt% of a non-hydrolyzable silane coupling agent and refluxed for 3-300 minutes to form a nanometer-thick coupling agent layer on the metal surface. The organic solvent in the present invention should be anhydrous (or it is understood that water is an unavoidable impurity, for example, the water content should be at least less than 0.5%, 0.3%, 0.1%, 0.05%, 0.02%, 0.01%, etc.) and the anhydrous organic solvent is a mixture of one or more of an alcohol solvent, an alcohol solvent, an ether solvent, an ester solvent, a nitrile solvent, a halogenated alkane solvent, an alkane solvent, ethanol, methanol, isopropanol, dichloromethane, acetonitrile, and acetone. Before use, the impurity water in the organic solvent can be further eliminated by reflux water separation, adsorption dehydration, drying dehydration, etc.
[0050] In the prior art, the silane coupling agent is usually dissolved in an aqueous solvent and applied to the metal surface (such as spraying), which leads to poor uniformity of spraying and a large coating thickness. In this patent, since the silane coupling agent solution does not contain water and has not been hydrolyzed, its reaction degree with the metal surface is significantly suppressed. Therefore, it is loaded on the metal surface by reflux, which ensures the uniformity of loading on the one hand, and the thickness of the silane coupling agent layer obtained by loading in this way is also significantly less than that of conventional technology.
[0051] Finally, the metal substrate after reflux treatment is dried and baked at 105°C for 10 to 120 minutes. On the one hand, the solvent can be removed, and on the other hand, the condensation between silanol groups caused by extremely small amounts of unavoidable water or the condensation between silanol groups and siloxane can be caused to cross-link the coupling agent layer on the metal surface.
[0052] In a preferred embodiment, the polished metal substrate is placed in an organic solvent for a dehydration step. By utilizing the property that the organic solvent can form a low azeotropic point with water, a water separator is installed in the reflux device, and the metal substrate is first refluxed for 30-120 minutes to remove the water adsorbed on the metal substrate to prevent the water from causing hydrolysis of the coupling agent in the organic solvent.
[0053] A metal-resin composite is a composite of resin on the other side of the modified layer on the metal treated with the surface silane coupling agent. The resin is a single type of resin or a resin composition; the resin contains a main resin and contains or does not contain a reinforcing material. The resin includes a single type of resin or a resin composition. Specifically, the present invention has a wide range of resins that can be selected, which can be thermoplastic resins or thermosetting resins, not limited to a few highly crystalline resins such as polyphenylene sulfide (PPS) and polybutylene terephthalate (PBT) reported in public, but also includes polyester, polyethylene, polypropylene, polystyrene, polyvinyl chloride, epoxy resin, polyamide, polyacetal, polycarbonate, modified polyphenylene ether, polyarylate, polyetherimide, polyamideimide, fluorine-containing resin, butyl resin and petroleum resin and other general resins, and their copolymers.
[0054] The metal-resin composite material prepared by the present invention can be used in printed circuit boards to achieve a good combination of resin materials and metals. The specific metal-resin composite material of the present invention can avoid the problem that water molecules increase the dielectric constant of the interface, thereby interfering with the high-speed transmission of high-frequency signals, so as to improve the reliability of the metal-resin composite substrate.
[0055] Example 1
[0056] In this embodiment, non-hydrolyzable 3-aminopropyltriethoxysilane KH550 is used to prepare a coupling agent layer with a nanometer thickness on the surface of a copper sheet, and an insert injection molding method is used to prepare a composite of the surface-treated copper sheet and polymethyl methacrylate (PMMA).
[0057] Step 1: electrochemical polishing of copper surface;
[0058] 1. Soak the copper sheet of size 1×15×50mm in acetone, ethanol and water for ultrasonic cleaning for 30 minutes.
[0059] 2. The cleaned copper sheet is placed in an electrolytic cell as an anode for polishing. The electrolyte contains 0.2wt% ascorbic acid, 0.3
[0060] 55wt% phosphoric acid solution of 55wt% ethylene thiourea, the polishing liquid is preheated to 55°C and then electrolyzed at a constant voltage of 10V for 10 minutes;
[0061] 3. Wash the polished copper sheet with water, blow dry with cold air, and store it in anhydrous organic solvent to prevent air oxidation of the metal surface.
[0062] Step 2: Copper surface combined with silane coupling agent
[0063] 1. Place the copper sheet polished in the first step in dichloromethane and ultrasonically clean it for 10 minutes.
[0064] 2. The copper sheet was placed in dichloromethane (containing about 50 ppm of water), and a water separator was installed in the reflux device to further remove the residual water. After reflux for 30 minutes, silane coupling agent KH550 was added to prepare a 0.2 wt% KH550 silane coupling agent anhydrous dichloromethane solution;
[0065] 3. Reflux for 180 minutes, take out the copper sheet, soak it in anhydrous dichloromethane, and ultrasonically clean it for 5 minutes;
[0066] Step 3: Cross-linking of copper surface with silane coupling agent
[0067] The copper sheet after the reflow treatment was dried and then placed in an oven at 105° C. for 20 minutes to cross-link the coupling agent layer on the surface of the copper sheet.
[0068] Step 4: Copper sheet and PMMA insert are injection molded to form a metal-resin composite
[0069] Insert the dried copper sheet into the injection molding mold, set the mold temperature to 155°C, the barrel temperature to 270°C, the injection pressure to 70 MPa, and the holding time to 16 seconds, and inject commercially available McLean injection-grade PMMA. After slowly cooling to room temperature, demold the copper sheet and PMMA composite that are firmly bonded together, and repeat the experiment 5 times.
[0070] Example 2
[0071] In this embodiment, non-hydrolyzed methyltriethoxysilane MTES is used to prepare a coupling agent layer with a nanometer thickness on the surface of a copper sheet, and an insert injection molding method is used to prepare a composite of the surface-treated copper sheet and PMMA.
[0072] Step 1: electrochemical polishing of copper surface;
[0073] 1. Soak the copper sheet of size 1×15×50mm in acetone, ethanol and water for ultrasonic cleaning for 30 minutes.
[0074] 2. The cleaned copper sheet is placed in an electrolytic cell as an anode for polishing. The electrolyte contains 0.2wt% ascorbic acid, 0.3
[0075] 55wt% phosphoric acid solution of 55wt% ethylene thiourea, the polishing liquid is preheated to 55°C and then electrolyzed at a constant voltage of 10V for 10 minutes;
[0076] 3. Wash the polished copper sheet with water, blow dry with cold air, and store it in anhydrous organic solvent to prevent air oxidation of the metal surface.
[0077] Step 2: Copper surface combined with silane coupling agent
[0078] 1. Place the copper sheet polished in the first step in dichloromethane and ultrasonically clean it for 10 minutes.
[0079] 2. The copper sheet was placed in dichloromethane (containing about 50 ppm of water), and a water separator was installed in the reflux device to further remove the residual water. After reflux for 30 minutes, silane coupling agent KH550 was added to prepare a 0.2 wt% KH550 silane coupling agent anhydrous dichloromethane solution;
[0080] 3. Reflux for 180 minutes, take out the copper sheet, soak it in anhydrous dichloromethane, and ultrasonically clean it for 5 minutes;
[0081] Step 3: Cross-linking of copper surface with silane coupling agent
[0082] The copper sheet after the reflow treatment was dried and then placed in an oven at 105° C. for 20 minutes to cross-link the coupling agent layer on the surface of the copper sheet.
[0083] Step 4: Copper sheet and PMMA insert are injection molded to form a metal-resin composite
[0084] Insert the dried copper sheet into the injection molding mold, set the mold temperature to 155°C, the barrel temperature to 270°C, the injection pressure to 70 MPa, and the holding time to 16 seconds, and inject commercially available McLean injection-grade PMMA. After slowly cooling to room temperature, demold the copper sheet and PMMA composite that are firmly bonded together, and repeat the experiment 5 times.
[0085] Example 3
[0086] In this embodiment, non-hydrolyzed KH550 and MTES are mixed on the surface of the copper sheet to prepare a coupling agent layer with a nanometer thickness, and the composite of the copper sheet with the surface treatment and PMMA is prepared by insert injection molding.
[0087] Step 1: electrochemical polishing of copper surface;
[0088] 1. Soak the copper sheet of size 1×15×50mm in acetone, ethanol and water for ultrasonic cleaning for 30 minutes.
[0089] 2. The cleaned copper sheet is placed in an electrolytic cell as an anode for polishing. The electrolyte contains 0.2wt% ascorbic acid, 0.3
[0090] 55wt% phosphoric acid solution of 55wt% ethylene thiourea, the polishing liquid is preheated to 55°C and then electrolyzed at a constant voltage of 10V for 10 minutes;
[0091] 3. Wash the polished copper sheet with water, blow dry with cold air, and store it in anhydrous organic solvent to prevent air oxidation of the metal surface.
[0092] Step 2: Copper surface combined with silane coupling agent
[0093] 1. Place the copper sheet after the first step of polishing in dichloromethane (containing about 50 ppm of water) and ultrasonically clean it for 10 minutes.
[0094] 2. Place the copper sheet in dichloromethane and install a water separator in the reflux device to further remove the residual water.
[0095] After refluxing for 30 minutes, a silane coupling agent KH550 was added to prepare a 0.2 wt % KH550 silane coupling agent anhydrous dichloromethane solution;
[0096] 3. Reflux for 180 minutes, take out the copper sheet, soak it in anhydrous dichloromethane, and ultrasonically clean it for 5 minutes;
[0097] Step 3: Cross-linking of copper surface with silane coupling agent
[0098] The copper sheet after the reflow treatment was dried and then placed in an oven at 105° C. for 20 minutes to cross-link the coupling agent layer on the surface of the copper sheet.
[0099] Step 4: Copper sheet and PMMA insert are injection molded to form a metal-resin composite
[0100] Insert the dried copper sheet into the injection molding mold, set the mold temperature to 155°C, the barrel temperature to 270°C, the injection pressure to 70 MPa, and the holding time to 16 seconds, and inject commercially available McLean injection-grade PMMA. After slowly cooling to room temperature, demold the copper sheet and PMMA composite that are firmly bonded together, and repeat the experiment 5 times.
[0101] Comparative Example 1
[0102] In this comparative example, no coupling agent is used, and only the surface of the copper sheet is polished, and the composite of the copper sheet and PMMA is prepared by insert injection molding.
[0103] Step 1: electrochemical polishing of copper surface;
[0104] 1. Soak the copper sheet of size 1×15×50mm in acetone, ethanol and water for ultrasonic cleaning for 30 minutes.
[0105] 2. The cleaned copper sheet is placed in an electrolytic cell as an anode for polishing. The electrolyte contains 0.2wt% ascorbic acid, 0.3
[0106] 55wt% phosphoric acid solution of 55wt% ethylene thiourea, the polishing liquid is preheated to 55°C and then electrolyzed at a constant voltage of 10V for 10 minutes;
[0107] 3. Wash the polished copper sheet with water, blow dry with cold air, and store it in anhydrous organic solvent to prevent air oxidation of the metal surface.
[0108] Step 2: Copper surface reflow control treatment
[0109] 1. Place the copper sheet polished in the first step in dichloromethane and ultrasonically clean it for 10 minutes.
[0110] 2. Place the copper sheet in dichloromethane, install a water separator in the reflux device, and reflux for 210 minutes;
[0111] 3. Take out the copper sheet and soak it in anhydrous dichloromethane and ultrasonically clean it for 5 minutes;
[0112] Step 3: Cross-linking of copper surface with silane coupling agent
[0113] The copper sheet after the reflow treatment was dried and then placed in an oven at 105° C. for 20 minutes to cross-link the coupling agent layer on the surface of the copper sheet.
[0114] Step 4: Copper sheet and PMMA insert are injection molded to form a metal-resin composite
[0115] Insert the dried copper sheet into the injection molding mold, set the mold temperature to 155°C, the barrel temperature to 270°C, the injection pressure to 70 MPa, and the holding time to 16 seconds, and inject commercially available McLean injection-grade PMMA. After cooling to room temperature, demold the copper sheet and PMMA composite that are firmly combined together, and repeat the experiment 5 times.
[0116] Comparative Example 2
[0117] In this embodiment, hydrolyzed KH550 is used to prepare a coupling agent layer on the surface of a copper sheet, and an insert injection molding method is used to prepare a composite of the surface-treated copper sheet and PMMA.
[0118] Step 1: electrochemical polishing of copper surface;
[0119] 1. Soak the copper sheet of size 1×15×50mm in acetone, ethanol and water for ultrasonic cleaning for 30 minutes.
[0120] 2. The cleaned copper sheet is placed in an electrolytic cell as an anode for polishing. The electrolyte contains 0.2wt% ascorbic acid, 0.3
[0121] 55wt% phosphoric acid solution of 55wt% ethylene thiourea, the polishing liquid is preheated to 55°C and then electrolyzed at a constant voltage of 10V for 10 minutes;
[0122] 3. Wash the polished copper sheet with water, blow dry with cold air, and store it in anhydrous organic solvent to prevent air oxidation of the metal surface.
[0123] Step 2: Copper surface combined with silane coupling agent
[0124] 1. Prepare silane coupling agent; weigh an appropriate amount of KH550, add 95% ethanol to prepare a 0.5wt% KH550 ethanol / water (95 / 5) solution, then add glacial acetic acid dropwise to adjust the pH value of the solution to 3, stir and hydrolyze at room temperature 25°C for 30 minutes to obtain a silane coupling agent treatment solution;
[0125] 2. Put the silane coupling agent treatment liquid into a spray pot, and spray it evenly on the surface of the copper sheet after the first step of polishing at room temperature of 25°C. The amount of coupling agent treatment liquid sprayed is about 20mL / m 2 Copper sheet, immediately use a stainless steel metal rod to roll the coupling agent treatment liquid evenly on the surface of the copper sheet after spraying. After waiting for 1 minute, use a hair dryer to blow cold air to remove the solvent on the surface of the copper sheet;
[0126] Step 3: Cross-linking of copper surface with silane coupling agent
[0127] The copper sheet coated with the coupling agent was placed in an oven at 105° C. and baked for 20 minutes to cross-link the coupling agent layer on the surface of the copper sheet.
[0128] Step 4: Copper sheet and PMMA insert are injection molded to form a metal-resin composite
[0129] Insert the dried copper sheet into the injection molding mold, set the mold temperature to 155°C, the barrel temperature to 270°C, the injection pressure to 70 MPa, and the holding time to 16 seconds, and inject commercially available McLean injection-grade PMMA. After cooling to room temperature, demold the copper sheet and PMMA composite that are firmly combined together, and repeat the experiment 5 times.
[0130] The surface metal-resin composite material interface bonding strength is quantitatively characterized by measuring the shear strength of the metal-resin insert injection molding composite according to the industry standard ISO19095; the compatibility of the metal and resin of the silane coupling agent layer is quantitatively characterized by measuring the water contact angle on the metal material surface; the anti-oxidation effect of the silane coupling agent layer on the metal is determined according to the method described in patent CN111962082 A, the metal is placed in an oven with a set temperature of 150°C and baked for 30 minutes, and the oxidation of the metal surface is observed, and the anti-oxidation effect is graded and evaluated in four levels: good, good, general and poor.
[0131] The test results of the embodiments of the present invention and the comparative examples are listed in the following table
[0132] Table 1 Test results of various properties of samples
[0133]
[0134] XPS depth analysis method was used to detect that the thickness of the silane coupling agent layer on the surface of the copper sheet in Example 1 was only 20 nm. As listed in Table 1, the interface bonding strength of the copper and PMMA composite treated with non-hydrolyzed KH550 in Example 1 was 19.94 MPa according to the ISO19095 measurement method, and the average value of 5 measurements was 19.94 MPa. It was 67.7% higher than the interface strength of 11.89 MPa of the copper and PMMA composite without coupling agent treatment in Comparative Example 1; and 50.7% higher than the interface strength of 13.23 MPa of the copper and PMMA composite treated with hydrolyzed KH550 in Comparative Example 2.
[0135] The closer the water contact angle of the metal surface treated with the coupling agent is to the contact angle of the organic resin, the better the compatibility of the metal and the resin, and the easier it is for the organic resin to infiltrate the metal surface during processing, achieving close contact with the coupling agent at the molecular level, and providing space guarantee for further bonding reactions between the resin molecules and the coupling agent functional groups. Since the water contact angle of PMMA is 74.2°, different types of coupling agents are used in the compounding of Example 3, so that the water contact angle of the copper sheet is very close to that of PMMA, so that the interface strength of the copper and PMMA composite is further improved to 20.48MPa.
[0136] Since the unhydrolyzed silane coupling agent in Examples 1, 2, and 3 fully reacts with the hydroxyl groups on the metal surface, not only is the coupling agent evenly distributed on the metal surface, but the nanometer-thick coupling agent layer is also endowed with better anti-oxidation properties than the hydrolyzed silane coupling agent layer in Comparative Example 2.
[0137] Parameter impact comparison experiment:
[0138] The present invention also investigates the influence of different reflux reaction times of non-hydrolyzable silane coupling agents on the surface properties of the obtained metal materials. The reflux time of KH550 in Example 1 was changed to 30 minutes, 90 minutes, and 240 minutes, and the interface strengths of the treated copper and PMMA composite were 15.01MPa, 16.20MPa, and 19.00MPa, respectively; the anti-oxidation effect of the silane coupling agent layer on copper was general, good, and good, respectively. Since the condensation reaction of the non-hydrolyzable silane coupling agent in anhydrous organic solvents and hydroxyl groups on the metal surface is more difficult than the condensation reaction of the hydrolyzed silane coupling agent with the hydroxyl groups on the metal surface, the non-hydrolyzable silane coupling agent requires a relatively long time to be fully spread on the metal surface. The interface strength of the metal and resin composite is positively correlated with the fullness of the coupling agent on the metal surface. At the same time, the anti-oxidation effect of the silane coupling agent layer on the metal is also positively correlated with the fullness of the coupling agent on the metal surface. Experiments show that in the reaction system of Example 1, it takes 180 minutes for KH550 to cover the copper surface. Further increasing the reflux time will further enhance the interfacial strength of the metal-resin composite and the anti-oxidation effect of the coupling agent layer on the metal.
[0139] Increasing the concentration of the non-hydrolyzed silane coupling agent in the anhydrous organic solvent can speed up the time it takes for the coupling agent to cover the metal surface. However, when the concentration of the silane coupling agent is too high, a physically adsorbed coupling agent layer is easily formed above the chemically bonded coupling agent layer, causing the interface strength of the metal-resin composite to decrease. For example, when the concentration of KH550 in Example 1 is changed to 2wt%, the interface strength of the treated copper and PMMA composite is 15.99MPa, which is 19.8% lower than the interface strength of 19.94MPa in Example 1.
[0140] Since the present invention solves the problem of continuous water release from the traditional coupling agent layer during material preparation and use, the metal material prepared by the above-mentioned metal surface coupling agent layer treatment method meets the requirements of high-frequency and high-speed signal transmission substrates represented by 6G.
Claims
1. A metal treated with a surface silane coupling agent, characterized in that: The surface includes a modification layer composed of a silane coupling agent, the thickness of the modification layer is in the range of 1-100 nm, and the hydrolyzable groups on the silane coupling agent on the main body of the modification layer are not hydrolyzed.
2. The metal treated with a surface silane coupling agent according to claim 1, characterized in that: The proportion of the silane coupling agent that has not been hydrolyzed is at least 90%, preferably 95%, and more preferably 98%; The thickness range is preferably 1-30 nm.
3. The metal treated with a surface silane coupling agent according to claim 1, characterized in that: The metal is copper, magnesium, aluminum, titanium, iron, zinc or an alloy thereof; the alloy refers to an alloy in which the corresponding metal accounts for more than 20wt%, more than 50wt%, preferably more than 80% by weight as the main component; the metal also includes metal or non-metal elements such as carbon, silicon, manganese, chromium, tungsten, molybdenum, phosphorus, titanium, vanadium, nickel, zirconium, boron, etc.; The general formula of the silane coupling agent is: Y-R'-Si(OR)3; Y is an organic group, which may be one of an amino group, a nitro group, a carboxyl group, an ester group, a hydroxyl group, an alkenyl group, an ether group, a sulfonic acid group, a mercapto group, an acryloxy group, a peroxyurea group, and a carbonyl alkoxy group; R' can be H or a branched or unbranched alkyl group containing 1 to 20 carbon atoms; R can be an alkoxy group, an aryloxy group, an acyl group, or a chloro group.
4. A metal-resin composite, characterized in that: The other side of the modified layer on the metal treated with the silane coupling agent according to claim 1 is compounded with a resin.
5. The metal-resin composite according to claim 4, wherein: The resin is a single type of resin or a resin composition; the resin includes a main resin and may or may not include a reinforcing material.
6. The method for producing a metal treated with a surface silane coupling agent according to claim 1, characterized in that: The steps include: Step 1, polishing the metal surface; Step 2, placing the obtained metal in an anhydrous organic solvent containing a silane coupling agent for a temperature-raising reflux reaction; the water content in the organic solvent is less than 0.1%; Step 3, the metal is heated after the reaction is completed.
7. The method for producing a metal treated with a silane coupling agent on the surface according to claim 6, characterized in that: The concentration range of the silane coupling agent in the anhydrous organic solvent is 0.001-1wt%; the temperature rise reflux reaction time is 3-300min, preferably 100-240min.
8. The method for producing a metal treated with a silane coupling agent on the surface according to claim 6, characterized in that: Before the polishing treatment, the step of pre-treating the metal is also included, and the pre-treatment step includes one of dewaxing, degreasing, activation, and cleaning; and after the polishing treatment, the metal can also be placed in an organic solvent for reflux to remove residual water.
9. A method for processing a metal-resin composite, comprising the following steps: placing a surface-treated metal in a mold, setting the mold temperature to a temperature above the glass transition temperature of the resin and below the melting temperature, and then injecting the resin into the mold to combine with the metal to form a metal-resin composite material; leaving the metal-resin composite material in the mold, allowing the metal-resin composite material to cool from its original temperature to below the glass transition temperature of the resin material before demolding.
10. A printed circuit board substrate for high-frequency and high-speed signal transmission, characterized in that: The metal-resin composite material according to claim 9 is included.
Citation Information
Patent Citations
Method for relieving copper printed circuit board solder resist cracking
CN103717011A
Cited By
Metal and resin joint integrated composite material
CN119773278A
Ultra-low profile metal foil with high peel strength and circuit board
CN120843002A